2014
DOI: 10.1007/s40415-014-0092-z
|View full text |Cite
|
Sign up to set email alerts
|

Response of cotton crop to exogenous application of glycinebetaine under sufficient and scarce water conditions

Abstract: Irrigation water is the basic resource to exploit the potential of cotton crop under an arid or a semi-arid environment. Under limited water conditions, various compatible solutes like glycinebetaine are being used to ameliorate the drought stress. Exogenous application of glycinebetaine (GB): GB 1 (100 mg L-1), GB 0 (no application) was done in adequate water (DS 0) and in drought stress condition (DS 1) at arid environment during the growing seasons of years 2009 and 2010. Results demonstrated that applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…14 From choline, after several steps, betaine phytocompound is formed, which plays a significant role in abiotic stress tolerance. [36][37][38][39] Clinical application has revealed that betaine can heal wounds, can be used in nutritional supplements and seizure controllers, and exerts anti-nephrotoxic effects. 40,41 The phytocompounds biosynthesized from the glycerophospholipid pathway (such as choline, o-phosphocholine, betaine, o-phosphoryl-ethanolamine) were higher in YT71/210 and F172 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…14 From choline, after several steps, betaine phytocompound is formed, which plays a significant role in abiotic stress tolerance. [36][37][38][39] Clinical application has revealed that betaine can heal wounds, can be used in nutritional supplements and seizure controllers, and exerts anti-nephrotoxic effects. 40,41 The phytocompounds biosynthesized from the glycerophospholipid pathway (such as choline, o-phosphocholine, betaine, o-phosphoryl-ethanolamine) were higher in YT71/210 and F172 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cotton (Gossypium spp.) is an economically important fiber crop grown in over 80 countries worldwide, mainly for use in the textile industry [1][2][3]. In 2019, global production of cotton exceeded 82 million tons, harvested from a >38-million-hectare cultivation area, with an estimated value of $74.4 billion dollars [4].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis was not performed because the dataset was comprised by one only haplotype 2. The selection analysis was not carried out for the CLRDV-typical-SA isolates because at least three different haplotypes are required.…”
mentioning
confidence: 99%
“…Likewise, Agboma et al (1997a,b) found that exogenous application of GB was indeed involved in the maintenance of a higher yield in maize and sorghum grains and tobacco leaves and resulted in improved water-use efficiency. GB was found to have a positive effect on yield also on soybean (Agboma et al, 1997b), common beans (Xing and Rajashekar, 1999), wheat (Agboma et al, 1997a), sunflower (Hussain et al, 2008), and cotton (Ahmad et al, 2014). Moreover, Park et al found that genetically engineered GB (2004) and exogenously applied GB (2006) increased the tolerance of tomato plants to chilling stress.…”
Section: Introductionmentioning
confidence: 99%